Impact of the COVID-19 Pandemic on the Surgical Activity within the Neurosurgery Department of the Hassan II Regional Hospital in Agadir - Elhairech, Dahmane; Kanazy, Saloua; Banga, Soukaina; Bouhrouje, Imane; Amghar, Meryem; Elkadmiri, Nadia; Mohammed, Lmejatti (International Journal of Innovative Research in Medical Science, 2022)
Introduction: Following the viral pandemic of COVID-19 in Morocco, the elective neurosurgical activity was stopped from March 30, 2020. Before the resumption of the unscheduled interventions, a quantitative assessment of the reduction of activity seems necessary. The objective of our study was to evaluate the reduction in neurosurgical activity during the period of the health crisis related to the COVID-19 pandemic, compared with the same period in 2019. Material and methods: We compared the number of neurosurgical procedures performed in the neurosurgical department at the regional hospital of Agadir during the health crisis from March 30, 2020 to July 31, 2020 compared to the same reference period of the previous year, and the types of surgery were collected and grouped into 15 categories. Results: A decrease in overall neurosurgical activity of 57, 18% was observed between 2019 and 2020 (383 and 219 procedures respectively). Emergency and neuro-oncology activity decreased by 63.93% and 29%. To make up for the shifted operative program, approximately 335 hours of intervention will have to be rescheduled. Conclusion: A drastic decrease in neurosurgical activity in the neurosurgical department at the regional hospital of Agadir was recorded following the confinement and postponement of elective surgery. During this period, the medical and paramedical staff was requested to participate in the management of patients with COVID 19.